(untitled) (Law and Safety, 2023)
The issue of interpretation of Part 3 of Art. 404 of the Criminal Procedure Code of Ukraine regarding the initiative of the court of appeal in the examination of evidence has been investigated: at the request of the parties to the court proceedings, the court of appeal is obliged to re-examine the circumstances established during criminal proceedings, provided that they were not fully or with violations investigated by the court of first instance, and may examine evidence which was not investigated by the court of first instance, only if the parties to the court proceedings request such examination. This is due to the opposite interpretation of this provision by the courts, including the Criminal Court of Cassation of the Supreme Court. The accuracy of the literal interpretation of this provision has been argued. Taking into account the peculiarities of proof at the stage of appellate proceedings, in particular, the controlling nature and dependence on the positions of the parties to criminal proceedings, part 3 of Article 404 of the Criminal Procedure Code of Ukraine should be interpreted as follows: when the court of appeal examines circumstances or evidence without a request of a party to criminal proceedings, it thereby goes beyond the scope of the complaint; if the court of appeal goes beyond the scope of the complaint, it is obliged to comply with the restrictions provided for in part 2 of Article 404 of the Criminal Procedure Code of Ukraine. The conclusion has been made that examination of evidence by the court of appeal on its own initiative, without a relevant request from a party to the proceedings, to establish certain circumstances to be proved or to provide a different assessment of certain evidence which was assessed by the local court, when considering an appeal filed to worsen the position of the accused, is a violation of the principle of competition between the parties and freedom to present their evidence and prove their conviction before the court, as set out in Art. 22 of the Criminal Procedure Code of Ukraine of the principle of adversarial nature of the parties and their freedom to present their evidence and prove their conviction before the court, and may indicate a lack of impartiality and accusatory bias of the court in a particular criminal proceeding.